Body composition and nutritional status in preoperative patients with refractory chronic constipation - Lei, Qiucheng; Wang, Xinying; Huang, Yingchun; Bi, Jingcheng; Liu, Sitong; Li, Pei; Jiang, Jun; Li, Ning (Progress in Nutrition, 2017)
Background/Aims: Altered body composition and malnutrition have been reported in some chronic diseases. However, no studies have examined the body composition and nutritional status in patients with refractory chronic constipation. The present study aimed to assess these two aspects in preoperative patients with refractory chronic constipation. Methods: One hundred seven patients with refractory chronic constipation, aged 18 to 63 years, and 133 healthy age-matched controls were enrolled. Assessment of body composition and nutritional status included anthropometry, biological nutritional parameters, and bioelectrical impedance analysis. Results: Preoperative patients with refractory chronic constipation and healthy subjects did not differ according to age or sex. Muscle mass, fat mass, fat-free mass, percent of body fat, fat mass index, and fat-free mass index were lower in the refractory chronic constipation group than in the control group. Fat mass index and fat-free mass index correlated significantly with body mass index in both male and female patients with refractory chronic constipation. No correlations were found between biological nutritional parameters and fat mass index or fat-free mass index, except for fat-free mass index in men. Based on body mass index and albumin, prealbumin, and transferrin levels, malnutrition existed in 28.04%, 0%, 37.38%, and 16.82%, respectively, of refractory chronic constipation patients. Conclusions: Parameters of body composition were worse in refractory chronic constipation patients than healthy participants, and several patients experienced malnutrition to some extent. Abnormalities in fat mass index and fat-free mass index might predict the nutritional status of patients with refractory chronic constipation.